PERANCANGAN MESIN PENGGILING KOPI TIPE VERTICAL GRINDING DENGAN KAPASITAS 70 KG/JAM - Ivan Eko Buwono, Ivan (2020)
Indonesian Coffee is the one of the most famous thing in Indonesia Indonesia is being famous by the characteristic of the coffee. However in Indonesia, the demand of coffee production is quite high. It makes Indonesia is difficult to fulfill the demand of the consument because the lack of Technology development on production industry. For that reason, the author have an idea to make a new type of Coffee Grinding Machine with Vertical Grinding type on production process that can increase the productivity of Mid-Low Coffee Factory. The design process is chosen based by the specification set by the author Type of the coffee bean that will be grinded is Tropical Indonesian Coffee Bean. Based on designing process and calculation process , engine dimension that have been designed is 630 mm x 630 mm x 1568 mm. And then blade that will be used for grinding is conical burr grinder with the spin speed by 150 RPM. Output Power of Motor value is 10,425 kVA, Power on Blade Grinder value is 2,6 kW, Transmission Power value is 5,74 kW with mechanical efficiency value is 0,45. The transmission that used on this machine is using Motor to Coupling transmission. There is an addons a filter to maximize the coffee production with hole size 0.1. Frame that use ST-37 material and Burr Grinder that use AISI 304 material have been analyzed and safe for construction.